Implementasi LKS Tabela untuk Meningkatkan Keterampilan Proses Sains Siswa SD - Rita Rahmaniati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The study aimed to (1) describe the science process activities of the fifth-grade students of SD Muhammadiyah Palangkaraya during learning by using the LAB Tabela (3) to find out the improvement of science processes of Muhammadiyah elementary school students in Palangkaraya city. The subjects in this study were all 27th-grade students of Muhammadiyah Elementary School in Palangkaraya, Central Kalimantan. The research method used by researchers was to use the class action research method with two cycles. The analysis technique in this study uses qualitative and quantitative data analysis. The results of the study show that the science process activities of students in learning using the LKS Tabela on average 2.92 are sufficient in the first cycle and the second cycle the excellent category is the average score of 3.79, and the results of the science process test showed an increase from the average pretest of 59.75 to an average of 89.5 in posttest, N gain of 0.82 in the high category. Through learning by using Tabela LKS able to improve learning outcomes and science process skills of students.